IMPACTS OF MARITAL CONFLICTS ON THE ACADEMIC PERFORMANCE OF SECONDARY SCHOOL STUDENTS IN OYO TOWNSHIP (UNIZIK Journal of Educational Management and Policy, 2026)
This research investigated the impact of marital conflicts on the academic performance ofsecondary school students. The population for the study comprised all secondary school teachersin Oyo township. The the sample for the study consisted of 200 secondary school students whichwas composed in multi-stages. Two hypotheses were formulated and tested at 0.05 alpha levelof significance. Questionnaire was the instrument used for data collection. The result revealedamong others that the marital conflicts has significant influence on the academic performance ofsecondary school students based on gender (r =3.11 ., p
Keywords: Marriage, Conflict, Marital conflict, Academic performance, Parents